3x+2(5x+4)=43

Simple and best practice solution for 3x+2(5x+4)=43 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+2(5x+4)=43 equation:


Simplifying
3x + 2(5x + 4) = 43

Reorder the terms:
3x + 2(4 + 5x) = 43
3x + (4 * 2 + 5x * 2) = 43
3x + (8 + 10x) = 43

Reorder the terms:
8 + 3x + 10x = 43

Combine like terms: 3x + 10x = 13x
8 + 13x = 43

Solving
8 + 13x = 43

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + 13x = 43 + -8

Combine like terms: 8 + -8 = 0
0 + 13x = 43 + -8
13x = 43 + -8

Combine like terms: 43 + -8 = 35
13x = 35

Divide each side by '13'.
x = 2.692307692

Simplifying
x = 2.692307692

See similar equations:

| 7e^5x+8=0.23 | | 8x^2(2x+9)+(2x+9)=0 | | a/10-8=24 | | 5x+2x-3=17 | | 28-2c=6c+4 | | 12x^2-x=16x+40 | | 2p^2+6p+3=0 | | 180=(6x-19)+(3x+32) | | -4r^2+3+r=0 | | 2w+17=21+3w | | 12n+25=-35 | | 6r+4=5r-8 | | 6x-1=4x+27 | | 2y-16=y-6 | | 4r^3=r+3 | | (74x-67y)-(56x+8y)= | | 8x^2+45x+58=0 | | 4y+14=7y+1 | | -4.4s+6.2=8.8s | | 3a^2-6ab+3b^2=0 | | 3-2(3x+1)=3x-(x+3) | | 1.33*n=12 | | 1.33*10=12 | | ln(20)-ln(4)= | | f(x)=x^2+10x+15 | | a^2b-4abc+4bc^2=0 | | x=-2.43902439 | | v/6+2=1 | | 3x+7y=155 | | -6.0+0.05x=5.30 | | -1+3d=0 | | 6*o= |

Equations solver categories